2009
DOI: 10.1080/09585190802673528
|View full text |Cite
|
Sign up to set email alerts
|

Personnel knowledge of the pay system, pay satisfaction and pay effectiveness: evidence from Finnish personnel funds

Abstract: Using data collected from over 1,000 individuals in 30 Finnish personnel funds, we study the links between pay knowledge, pay satisfaction and pay effectiveness. We find consistent evidence that higher levels of pay knowledge are associated with improved pay satisfaction and perceived pay effectiveness at the organizational level. We find that pay knowledge has an independent impact on organizational outcomes, rather than being mediated through pay satisfaction. Finally, comparing measures of actual pay knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…It is now more evident that employees have the opportunity to make suggestions on the structure of the reward system within their own organisations (Allen & Killman, 2001). Sweins, Kalmi and Hulkko-Nyman (2009) propose that organisations should be obligated to explain to their employees how the reward system and structure works. Greater knowledge of the system is crucial in ensuring that employees understand what is expected of them.…”
Section: Rewardsmentioning
confidence: 99%
“…It is now more evident that employees have the opportunity to make suggestions on the structure of the reward system within their own organisations (Allen & Killman, 2001). Sweins, Kalmi and Hulkko-Nyman (2009) propose that organisations should be obligated to explain to their employees how the reward system and structure works. Greater knowledge of the system is crucial in ensuring that employees understand what is expected of them.…”
Section: Rewardsmentioning
confidence: 99%
“…Earlier studies on Finland have focused on more limited sets of financial participation practices (e.g. Piekkola 2005;Jones et al 2006; Kauhanen and Piekkola 2006;Sweins et al 2009). By assembling new and wideranging data on financial participation practices in Finnish manufacturing companies, we undertake the most comprehensive evaluation of the prevalence and determinants of financial participation for Finland to date.…”
Section: Introductionmentioning
confidence: 99%
“…Personnel funds differ from all other schemes in the sense that they are tightly regulated 1 For a closer description on personnel funds, see Sweins et al (2009). 5 and supervised by the Ministry of Labour. The main idea of the funds is that they receive payments (profit-shares) according to specified performance criteria.…”
mentioning
confidence: 99%
“…In a study by Anvari et al (2011), the authors found a positive relationship between strategic compensation practices and perceived fulfilment of psychological contract. Sweins et al (2009) proposed that organisations should be obliged to explain to employees how their reward system works, as knowledge of the system is crucial in ensuring employees commitment (Hoole, Hotz, 2016). In Nigeria, Maycock (2014) empirically found that employees prefer working with individual performance related pay than in teams, and that performance related pay improved individual and organisational performances.…”
Section: Empirical Studiesmentioning
confidence: 99%